Laryngopharyngeal Reflux in Pregnancy - Worapong Vejvechaneyom (The Royal Thai College of Obstetricians and Gynaecologists, 2011)
Laryngopharyngeal reflux (LPR) is the retrograde movement of gastric contents (acid and enzymes such as pepsin) in to the upper aerodigestive tract especially the laryngopharynx leading to symptoms referable to inflammatory diseases of larynx/ hypopharynx/throat/nose & paranasal sinuses/mouth/middle ears. Typical symptoms of LPR include hoarseness, globus pharyngeus (sensation of lump in the throat), cough, excessive mucus in the throat with throat clearing, and mild dysphagia. Sometime, the LPR patients including the pregnant women with LPR also have the excessive saliva and may occasionally complain of a sudden filling of the throat with bitter or salty saliva (water brash).LPR is related to gastroesophageal reflux disease (GERD), but is not identical to it. Patients with GERD may have no LPR, and conversely, patients with LPR may have no GERD. Most patients are relatively unaware of LPR with only 30 percent reporting heartburn.(1) There are no certain criteria that reliably demonstrate a causal link between acid reflux and LPR symptoms. In fact, the validity of reflux as a cause of LPR symptoms, in the absence of symptoms of GERD, has been called into question. Thus, it is likely that some patients are mistakenly diagnosed with LPR, and investigation of other causes of upper airway symptoms (such as allergy, sinus, or other causes of cough, etc) should be considered for patients who fail to respond to LPR management.